Variant selection in laser powder bed fusion of non-spherical Ti-6Al-4V powder. (1st June 2023) - Asherloo, Mohammadreza; Wu, Ziheng; Sabisch, Julian E.C.; Ghamarian, Iman; Rollett, Anthony D.; Mostafaei, Amir
Highlights: Coarse non-spherical powder locally decreases cooling rates during laser powder bed fusion. Locally lower cooling rates results in β/β grain boundary α variant selection. Self-accommodation was the main variant selection mechanism. Type 4 was the dominant α/α grain boundary variant. Category II variant cluster was analytically proved to be dominant. Abstract: The presence of α / α′ on prior β / β grain boundaries directly impacts the final mechanical properties of the titanium alloys. The β / β grain boundary variant selection of titanium alloys has been assumed to be unlikely owing to the high cooling rates in laser powder bed fusion (L-PBF). However, we hypothesize that powder characteristics such as morphology (non-spherical) and particle size (50–120 µm) could affect the initial variant selection in L-PBF processed Ti-6Al-4V alloy by locally altering the cooling rates. Despite the high cooling rate found in L-PBF, results showed the presence of β / β grain boundary α′ lath growth inside two adjacent prior β grains. Electron backscatter diffraction micrographs confirmed the presence of β / β grain boundary variant selection, and synchrotron X-ray high-speed imaging observation revealed the role of the " shadowing effect " on the locally decreased cooling rate because of keyhole depth reduction and the consequent β / β grain boundary α′ lath growth. The self-accommodation mechanism was the main variant selection driving force, and the most abundant α / α boundary variant was type 4 (63.26°//[ 10 ¯ 5 5 3 ¯ ]). The dominance of Category II α lath clusters associated with the type 4 α / α boundary variant was validated using the phenomenological theory of martensite transformations and analytical calculations, from which the stress needed for the β → α′ transformation was calculated. Graphical Abstract: Image, graphical abstract